Влияние криозащитных растворов и их компонентов на интенсивность процессов перекисного окисления липидов и антиоксидантную активность лейкоцитов при криоконсервировании - Khudyakov, Andrey N.; Polezhaeva, Tatyana V.; Zaitseva, Oksana O.; Laptev, Denis S.; Solomina, Olga N.; Kostyaev, Andrey A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2013)
Using chemiluminescence method it was shown that after addition of several cryoprotectants 1,2-propane diol (21% initial concentration hereinafter and added 1:1) and dimethyl sulfoxide (8%) to leukocyte suspension the level of LPO and antioxidant activity decreased. Presence of glycerol (7%) and hexa-methylene bis-tetra hydroxyethyl urea (30%) resulted in simultaneous stimulation of LPO and antioxidant systems. Hydroxyethylated starch (5.7%) and gelatine (molecular weight of 16,000; 7.5%) increase LPO. After storage in combined cryoprotective media at –10, –20 and –40°C the leukocytes revealed the activation of antioxidant systems on the background of stable LPO indices, that, probably, contributed to morphofunctional preservation of 75% of cells.